2019
DOI: 10.1111/cid.12848
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of peri‐implantitis and peri‐implant mucositis 17 to 23 (18.9) years postimplant placement

Abstract: PurposeTo evaluate the prevalence of peri‐implantitis (PI) and peri‐implant mucositis (PM) in a long‐term follow‐up with comparison among different PI and PM definitions, and to report on the incidence of PI.Materials and MethodsIn a retrospective clinical study five different PI and PM definitions were applied onto a population with 274 implants 17 to 23 years postimplant placement. Recommendations by the Eighth European Workshop on Periodontology (EWOP) were used as base reference. Clinical and radiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…The role of the clinical parameters on bone loss prediction is controversial as revealed by previous studies. The clinician should be cognisant of possible false-positive findings (Coli et al, 2017;Doornewaard et al, 2018;Hashim et al, 2018;Krebs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the clinical parameters on bone loss prediction is controversial as revealed by previous studies. The clinician should be cognisant of possible false-positive findings (Coli et al, 2017;Doornewaard et al, 2018;Hashim et al, 2018;Krebs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implant diseases are infective complications of surrounding dental implant tissues that often occurs [49], demonstrated a peri-implantitis incidence of 7.9% on implant level. Pjetursson et al [50] studied the 5-and 10-year survival of implant-supported fixed dental prostheses (FDPs) analyzing 32 studies that matched the criteria for the systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…They represent a high risk of implant failure. A recent study, with a long follow-up [ 49 ], demonstrated a peri-implantitis incidence of 7.9% on implant level.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning risk factors, they identified medium and medium-high evidence with respect to development of the illness in patients who are smokers, those without regular maintenance control, and those with diabetes mellitus (DM) or with a history of periodontitis [6]. In their retrospective clinical study by Krebs, it was found that the incidence of PI is 7.9% at the implant level and 13.2% at the patient level seventeen years after implant placement [7].…”
Section: Introductionmentioning
confidence: 99%